2014
DOI: 10.25105/jat.v1i2.4804
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kinerja Keuangan, Corporate Governance, Dan Kualitas Audit Terhadap Pengungkapan Corporate Social Responsibility

Abstract: <span class="fontstyle0">The purpose of this research is to determine the the influence of financial performance, corporate governance, and audit quality on corporate social responsibility disclosure. Data for this research were obtained from firm’s annual reports which is available on Indonesia Stock Exchange (IDX) sites. Samples used in this research are 139 manufacturing companies that listed on Indonesia Stock Exchange in period 2012. The Sampling technique used is purposive sampling method. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 0 publications
2
9
1
16
Order By: Relevance
“…Hal ini disebabkan salah satu tugas komite audit adalah untuk memastikan keandalan laporan, sehingga managemen perusahaan perlu untuk mengungkapkan tanggung jawab sosial dan lingkungan. Semakin besar ukuran komite audit, maka peran komite audit dalam mengendalikan dan memantau manajemen puncak akan semakin efektif (Iswandika et al, 2014;Krisna dan Suhardianto, 2016). Hipotesis yang digunakan adalah: H3 : Komite sudit berpengaruh positif terhadap pengungkapan tanggung jawab sosial perusahaan.…”
Section: Komite Audit Dan Pengungkapan Tanggung Jawab Sosial Perusahaanunclassified
See 1 more Smart Citation
“…Hal ini disebabkan salah satu tugas komite audit adalah untuk memastikan keandalan laporan, sehingga managemen perusahaan perlu untuk mengungkapkan tanggung jawab sosial dan lingkungan. Semakin besar ukuran komite audit, maka peran komite audit dalam mengendalikan dan memantau manajemen puncak akan semakin efektif (Iswandika et al, 2014;Krisna dan Suhardianto, 2016). Hipotesis yang digunakan adalah: H3 : Komite sudit berpengaruh positif terhadap pengungkapan tanggung jawab sosial perusahaan.…”
Section: Komite Audit Dan Pengungkapan Tanggung Jawab Sosial Perusahaanunclassified
“…Variabel ini diukur dengan membagi jumlah komisaris non eksekutif dengan total jumlah dewan komisaris dalam perusahaan (Ali dan Atan, 2013). Komite audit diukur dengan menggunakan proksi jumlah keanggotaan komite audit (Iswandika et al, 2014).…”
Section: Metode Penelitianunclassified
“…Profitability contributes positively to the disclosure of ISR. However, the other research found that profitability does not give any significant effect on the disclosure of ISR [6].…”
Section: Introductionmentioning
confidence: 85%
“…This paper presents a result of effects with some combines aspects from the previous researches by investigating some impact factors ISR disclosure, which has not been observed [4], [5], and [6]. The authors add stock value factor which is estimated as the impact factor of ISR disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional ownership is ownership of company shares owned by institutional investors, for example, such as the government, companies, banks, financial companies, etc. The indicator used to measure institutional ownership is the percentage of the number of shares owned by the institution of all outstanding share capital [7].…”
Section: B Institutional Ownershipmentioning
confidence: 99%